2021
DOI: 10.3390/toxins13040250
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Tetrodotoxin (TTX) in Trumpet Shell Charonia lampas from the Portuguese Coast

Abstract: Tetrodotoxin (TTX) is a potent neurotoxin, considered an emerging toxin in Europe where recently a safety limit of 44 µg TTX kg−1 was recommended by authorities. In this study, three specimens of the large gastropod trumpet shell Charonia lampas bought in a market in south Portugal were analyzed using a neuroblastoma cell (N2a) based assay and by LC-MS/MS. N2a toxicity was observed in the viscera of two individuals analyzed and LC-MS/MS showed very high concentrations of TTX (42.1 mg kg−1) and 4,9-anhydroTTX (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Hitherto, TTX and its more than 30 known analogs (TTXs) have been found in an impressive diversity of phylogenetically unrelated organisms (both terrestrial, e.g., amphibians, and aquatic, e.g., fish from the Tetraodontidae family, worms, cephalopods, gastropods, bivalves, see for example the review of Noguchi and Arakawa [3]). A new TTX-like analogue (m/z 318.1) was even recently reported in the gastropod Charonia lampas from the Portuguese coast [4]. However, these toxins are considered an emerging threat in Europe and in bivalves (see reviews [5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, TTX and its more than 30 known analogs (TTXs) have been found in an impressive diversity of phylogenetically unrelated organisms (both terrestrial, e.g., amphibians, and aquatic, e.g., fish from the Tetraodontidae family, worms, cephalopods, gastropods, bivalves, see for example the review of Noguchi and Arakawa [3]). A new TTX-like analogue (m/z 318.1) was even recently reported in the gastropod Charonia lampas from the Portuguese coast [4]. However, these toxins are considered an emerging threat in Europe and in bivalves (see reviews [5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…The specimen's digestive glands contained extremely high parent TTX and total TTXs levels, with reported concentrations of 315,000 and 1,319,000 µg/kg, respectively [25]. Further investigations in Portuguese and Moroccan gastropods revealed the presence of TTXs at quantifiable levels in three more species, Steromphala umbilicalis (formerly Gibbula umbilicalis), Phorcus lineatus (formerly Monodonta lineata), and Onchidella celtica, as well as in additional C. lampas specimens, some at high concentrations [7,73,84,85]. In general, it appears that higher TTXs contents are detected in the viscera of gastropods, potentially indicating a dietary route of accumulation; however, in some species, TTXs are exclusively detected in the flesh instead, which suggests the possible existence of alternative TTX binding mechanisms or sources [37].…”
Section: Ttxs In Gastropods and Echinodermsmentioning
confidence: 98%
“…Until recently, TTX was believed to be confined to East Asia, but recent studies have shown that fish containing the toxin have been found in other regions of the Pacific and the Indian Ocean, as well as the Mediterranean Sea [3]. There are also many poisoning cases reported from countries, such as Australia [85,167,168], Brazil [169,170], Mexico [171], Oman [172], Madagascar [173], Reunion Island [174], Egypt [175], and Morocco [176].…”
Section: Global Cases Of Ttx Intoxication In Humansmentioning
confidence: 99%
“…Some marine gastropods are, in fact, carnivorous and may wellfeed by scavenging (Taniyama et al, 2009;Wang et al, 2008) on TTX-bearing species, such as pufferfish (Noguchi et al, 2011). Costa et al (2021) linked the high amount of TTXs found in the viscera of a C. lampas specimen (42.1 and 56.3 mg/kg of TTX and 4,9-anhydroTTX, respectively) to the dietary habits of this gastropod, which feeds on starfish.…”
Section: Ttx Presence In Live Bivalve Mollusks and Causative Factors ...mentioning
confidence: 99%
“…Other records were mainly in various species from Asian countries , until 2007 when the toxins were discovered in a specimen of C. lampas lampas from Portugal, which was linked to a case of human intoxication following ingestion of the gastro-pod contaminated flesh (Rodriguez et al, 2008). Following a pattern of occurrence that can resemble that seen for bivalve mollusks, TTXs in gastropods are being reported more often in Europe, involving different species harvested from France, Morocco, Portugal, and Spain (Blanco et al, 2019;Costa et al, 2021;Hort et al, 2020;Silva et al, 2012Silva et al, , 2019; Table 2). Interestingly, the amounts of TTXs detected in marine gastropods are by far higher than those in bivalves (Table 1).…”
Section: Ttx Presence In Live Bivalve Mollusks and Causative Factors ...mentioning
confidence: 99%